Potensi Wisata Kulineri dan Pendidikan di Pesona Alam Dusun Sendang Kumitir Desa Kembang Arum Turi Sleman sebagai Daerah Tujuan Wisatawan - Wisnu Hadi (Media Wisata, 2017)
One of the tourism products in Yogyakarta which is now again a trend and developed is educational tours and culinary tours that can complement other tours such as natural attractions and culture. Because the natural and cultural tourism products are very much in Yogyakarta. A lot of information from the print and electronic media that interest tourism such as culinary and education are widely sold in the media because it is a very promising income and certainly increase the regional economic income. One of the educational and culinary tours is the Natural Enchantment Sendang Kumitir Hamlet that has the potential for culinary tourism and education. In this qualitative descriptive research, the researcher exposed the potential that supports tourism. SWOT analysis also explained that this tour should be developed by managers to be bigger because there is still enough land to expand the tour. From the results of the questionnaire data that tourists are enjoying the education and culinary tour because it is supported by the natural atmosphere that is still beautiful and cool because in the middle of the village and surrounded by bark garden is quite wide. In terms of service to tourists considered satisfactory in terms of attractiveness, facilities and human resources or managers in this case employees and owners of this attraction